2023
DOI: 10.1039/d2na00785a
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Ag/Cu/PEG nanofluids prepared when solids meet liquids in the gas phase

Abstract: Since the time of Faraday’s experiments, the optical response of plasmonic nanofluids has been tailored by the shape, size, concentration, and material of nanoparticles (NPs), or by mixing different types...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 67 publications
0
36
0
Order By: Relevance
“…6a–f present the temporal evolution of the PSDs of the population found via the LES technique, fitted with the assumption of log-normal distribution. 32,60,61 Since the LES technique cannot detect the tiny primary clusters without plasmon characteristics, the first detected Ag NPs in silicone oil have a diameter of ∼20 nm and we observe that Ag NPs continue to grow in silicone oil after the plasma is turned off (curves in orange color shifting towards larger diameters). Similar post-sputtering growth is also reported in the literature.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…6a–f present the temporal evolution of the PSDs of the population found via the LES technique, fitted with the assumption of log-normal distribution. 32,60,61 Since the LES technique cannot detect the tiny primary clusters without plasmon characteristics, the first detected Ag NPs in silicone oil have a diameter of ∼20 nm and we observe that Ag NPs continue to grow in silicone oil after the plasma is turned off (curves in orange color shifting towards larger diameters). Similar post-sputtering growth is also reported in the literature.…”
Section: Resultsmentioning
confidence: 82%
“…The LES observations might help to better understand the NP formation process during reactive magnetron sputtering deposition. 70 Moreover, the LES technique can also be implemented into other nanouid synthesis methods, such as electrode erosion using discharges in liquids, 71 evaporation in vacuum onto liquids, 72 sputteringbased Gas Aggregation cluster Source (GAS), 61 in a stopped-ow device during a chemical reduction. 52 Despite their lure as an efficient heat transfer strategy, 73 nanouids are still not in practice as the working uid due to the inconsistent experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…6a-6f present the temporal evolution of the PSDs of the population found via the LES technique, fitted with the assumption of log-normal distribution. 33,67,68 Since the LES technique cannot detect the tiny primary clusters without plasmon characteristics, the first detected Ag NPs in silicone oil have a diameter of ∼20 nm and we observe that Ag NPs continue to grow in silicone oil after the plasma is turned off (curves in orange color shifting towards larger diameters). Similar post-sputtering growth is also reported in the literature.…”
Section: Absorption Spectra and Repeatabilitymentioning
confidence: 80%
“…The LES observations might help to better understand the NP formation process during reactive magnetron sputtering deposition. 77 Moreover, the LES technique can also be implemented into other nanomaterial synthesis methods, such as electrode erosion using discharges in liquids, 78 evaporation in vacuum onto liquids, 79 sputtering-based Gas Aggregation cluster Source (GAS), 68 in a stopped-flow device during a chemical reduction. 60 Despite their lure as an efficient heat transfer strategy, 80 nanofluids are still not in practice as the working fluid due to the inconsistent experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we present a new sputter-based method to produce TiN, ZrN, and HfN nanofluids in one step. Conventional inert gas magnetron sputtering has for a long time been known as a method to produce metal/ceramics/polymer-based nanocomposite coatings, and it has also been adapted to produce NPs under elevated pressures. We have also shown that gas-aggregated NPs can be directly loaded into liquids to produce nanofluids, provided that the liquids are compatible with vacuum. , On the other hand, reactive sputtering was extensively used to deposit thin films of MeN, often requiring hot substrates or postdeposition annealing to produce thin films of high quality. Importantly, reactive sputtering was not known for the synthesis of nitride NPs until recently, when our group managed to produce TaNO NPs by sputtering the Ta target in gas mixtures of Ar and N 2 , opening a route toward the synthesis of other metal nitride NPs .…”
Section: Introductionmentioning
confidence: 99%